Human resource management practices and organizational injury rates - Turner, N.; Barling, J.; Dawson, J.F.; Deng, C.; Parker, Sharon; Patterson, M.G.; Stride, C.B. (2021)
Introduction: This study investigated the extent to which five human resource management (HRM) practices—systematic selection, extensive training, performance appraisal, high relative compensation, and empowerment—simultaneously predicted later organizational-level injury rates.